2009
DOI: 10.1080/00016340902971466
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous malformation as a consequence of a scar pregnancy

Abstract: A scar pregnancy is an ectopic pregnancy implanted in a previous lower segment cesarean scar, and the incidence of this complication may be expected to rise along with increasing cesarean section rates. Arteriovenous malformation of the uterus may be congenital, associated with early pregnancy loss, trophoblastic disease, or surgical procedures. We describe a case of uterine arteriovenous malformation as a consequence of a scar pregnancy, complicated by recurrent, serious bleeding. The condition was diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
1
14
1
Order By: Relevance
“…However, a longer follow‐up period due to slower β‐hCG decrease should be expected when this management is selected. Underlying conditions, such as arteriovenous malformation, should be investigated when the bleeding persists and immediate surgical measures should be taken . The success rate of the intervention may decrease with advanced pregnancies (Case 4) and with an underlying condition, such as arteriovenous malformation (Case 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, a longer follow‐up period due to slower β‐hCG decrease should be expected when this management is selected. Underlying conditions, such as arteriovenous malformation, should be investigated when the bleeding persists and immediate surgical measures should be taken . The success rate of the intervention may decrease with advanced pregnancies (Case 4) and with an underlying condition, such as arteriovenous malformation (Case 2).…”
Section: Discussionmentioning
confidence: 99%
“…More than half of these women have only had one prior cesarean delivery [5]. AVMs have been confirmed as arising from a prior cesarean scar ectopic implantation site [6]. This may result from failed obliteration of placental bed vessels in the absence of retained placental tissue.…”
Section: Resultsmentioning
confidence: 99%
“…An uteroplacental neovascularization pattern in the CSP may be another important factor in the determination of which form of treatment is appropriate. An AVM must be regarded as a likely consequence of a CSP; the diagnosis can be confirmed by finding trophoblastic tissue and abnormally dilated vessels in the resected Cesarean scar 18…”
Section: Discussionmentioning
confidence: 99%
“…A literature review showed only two case reports of CSPs complicated with AVMs17, 18 (Table 1). On the other hand, β‐hCG levels do not support a diagnosis of an AVM 18. No stepwise treatment strategy for CSP or related complications, such as AVMs, has been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation